Polyaniline based corrosion inhibitors for conventional organic coatings - Branimir Grgur; Branimir Jugović (Zaštita Materijala)
Corrosion protection using conventional coatings is the most used method. Application of polyaniline (PANI) as an inhibitor in conventional coating is based on its proven and well examined protective nature, with motivation for replacement of hazardous materials used as inhibitors. Experimental procedures for investigation of the influence of PANI in coatings are focused both on evaluation of physical properties of the coatings studied by FTIR, Raman and UV spectroscopy, thermogravimetric analysis, SEM and TEM microcopies, while the protective nature of the coating, applied at the first place on steel, is studied by accelerated corrosion testing using humidity and salt chamber, electrochemical impedance spectroscopy and polarization measurements upon immersion in corrosion media.